Conceptualizing and counteracting the bullying dynamic: Classroom and school contexts matter - Saarento, Silja (fi=Turun yliopisto|en=University of Turku|, 2015)
Guided by the social-ecological conceptualization of bullying, this thesis examines the implications of classroom and school contexts—that is, students’ shared microsystems—for peer-to-peer bullying and antibullying practices. Included are four original publications, three of which are empirical studies utilizing data from a large Finnish sample of students in the upper grade levels of elementary school. Both self- and peer reports of bullying and victimization are utilized, and the hierarchical nature of the data collected from students nested within school ecologies is accounted for by multilevel modeling techniques. The first objective of the thesis is to simultaneously examine risk factors for victimization at individual, classroom, and school levels (Study I). The second objective is to uncover the individual- and classroom-level working mechanisms of the KiVa antibullying program which has been shown to be effective in reducing bullying problems in Finnish schools (Study II). Thirdly, an overview of the extant literature on classroom- and school-level contributions to bullying and victimization is provided (Study III). Finally, attention is paid to the assessment of victimization and, more specifically, to how the classroom context influences the concordance between self- and peer reports of victimization (Study IV). Findings demonstrate the multiple ways in which contextual factors, and importantly students’ perceptions thereof, contribute to the bullying dynamic and efforts to counteract it. Whereas certain popular beliefs regarding the implications of classroom and school contexts do not receive support, the role of peer contextual factors and the significance of students’ perceptions of teachers’ attitudes toward bullying are highlighted. Directions for future research and school-based antibullying practices are suggested.

Luokka- ja koulukonteksteilla on väliä Kiusaamisen sosioekologisen käsitteellistämisen ohjaamana tämä väitöskirja tarkastelee luokka- ja koulukontekstien – oppilaiden yhteisten mikrosysteemien – merkityksiä vertaisten välillä tapahtuvalle kiusaamiselle ja kiusaamisenvastaisille toimenpiteille. Väitöskirja käsittää neljä alkuperäistä julkaisua. Näistä kolme ovat empiirisiä tutkimuksia, jotka perustuvat alakoulun ylempien luokka-asteiden oppilaista koostuvaan laajaan suomalaiseen aineistoon. Tutkimuksissa käytetään sekä oppilaiden itsearvioita että toveriarvioita kiusaamisesta ja kiusatuksi joutumisesta, ja koulumaailmaan sijoittuvan oppilasaineiston hierarkkinen luonne huomioidaan monitasomallinnuksen keinoin. Väitöskirjan ensimmäinen tavoite on samanaikaisesti tutkia yksilö-, luokka- ja koulutason riskitekijöiden yhteyksiä kiusatuksi joutumiseen (julkaisu I). Toisena tavoitteena on selvittää yksilö- ja luokkatason mekanismit, jotka selittävät kiusaamisenvastaisen KiVa Koulu -ohjelman vaikuttavuutta suomalaisissa kouluissa (julkaisu II). Kolmanneksi luodaan katsaus tähänastiseen tutkimukseen luokka- ja koulukontekstien merkityksistä kiusaamiselle ja kiusatuksi joutumiselle (julkaisu III). Lopuksi huomio kiinnitetään kiusaamisen mittaamiseen ja tarkemmin sanottuna siihen, miten luokkakonteksi vaikuttaa kiusatuksi joutumisen itsearvioiden ja toveriarvioiden yhteneväisyyteen (julkaisu IV). Tutkimustulokset ilmentävät niitä moninaisia merkityksiä, joita konteksteilla – ja erityisesti oppilaiden omilla käsityksillä konteksteistaan – on kiusaamisen dynamiikalle ja siihen puuttumiselle. Siinä missä jotkin yleiset uskomukset luokka- ja koulukontekstien vaikutuksista eivät saa tukea, tuloksissa korostuvat vertaisryhmän sosiaalisten tekijöiden vaikutukset sekä sen tärkeys, miten oppilaat uskovat opettajiensa suhtautuvan kiusaamiseen. Tulevaisuuden suuntaviivoja esitetään kiusaamisen tutkimukselle ja kiusaamisenvastaisille toimenpiteille kouluissa.